Repaying microcredit loans: A natural experiment on liability structure - Mahreen Mahmud (University of Kent, School of Economics, 2015)
Microcredit loans were traditionally extended to groups of people. However, there is no clear evidence that joint liability does lead to better borrower performance and recent years have seen a shift towards individual liability lending. Utilizing the exogenous shift from individual to joint liability lending by a microfinance organization in Pakistan, we find evidence of significant improvement in borrower discipline. Borrowers are about 0.6 times as likely to miss a payment in any given month under joint liability relative to individual liability. We also use the exogenous variation in number of months borrowers had till the expiry of their individual liability loans at the time of the shift to study the kind of groups they formed. More time that borrowers had, the more likely they were to form groups with people they knew from before and met weekly. The time that borrower had to form group also correlated positively with borrower discipline.
Keywords: D71; D82; G21; 330; Microfinance; Group lending; Joint liability